SEGREGATION OF RELIGIOUS IDENTITY: An Ethnography of Religion Pluralism and Cultural Trauma in the Tolaki Communities - Muhammad Alifuddin; Abdul Muiz Amir (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
This article aimed to determine segregation between Muslims and Christians in the Tolaki ethnic community, especially in the Wolasi and Lambuya Sub-districts, Southeast Sulawesi, Indonesia. The two areas are important to review, considering that the two populations, consisting of Muslims and Christians, come from the same ethnic group but differ in their response to religious pluralism. The method used is descriptive qualitative, utilizing observation and in-depth interviews. Furthermore, the data were analyzed using ethnography and historical approaches. The results show that the Tolaki ethnic group (Muslim and Christian) in the Lambuya community more openly responds to religious pluralism than the Wolasi community. In terms of historical perspective, the Wolasi community experienced cultural trauma from the history of Christianization during the Dutch colonies. This is because there were significant differences in perspective between religious believers, even though they were still in one ethnic group and family. In contrast, the Lambuya community prioritizes the interests of brotherhood relations within the same ethnicity and family. But the people in both subdistricts take local customs and cultures into account when trying to solve religious and social problems. If they don’t get along because of their different religions, Kalosara can help them work things out. This research suggests that combining faith and local wisdom is an alternative way to deal with social diversity.